1999
DOI: 10.1038/sj.cdd.4400506
|View full text |Cite
|
Sign up to set email alerts
|

bFGF inhibits the activation of caspase-3 and apoptosis of P19 embryonal carcinoma cells during neuronal differentiation

Abstract: P19 embryonal carcinoma (EC) cells undergo apoptosis during neuronal differentiation induced by all-trans retinoic acid (RA). Caspase-3-like proteases are activated and involved in the apoptosis of P19 EC cells during neuronal differentiation. 1 Recently it has been shown that growth factor signals protect against apoptosis by phosphorylation of Bad. Phosphorylated Bad, an apoptotic member of the Bcl-2 family, cannot bind to Bcl-x L and results in Bcl-x L homodimer formation and subsequent antiapoptotic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…We have noted that apoptosis during retinoic acid-induced ES differ- entiation was accompanied by increased expression of effector caspases 3 and 6. It has been reported previously that retinoic acid can induce activation of caspase-3 and cause apoptosis during neural differentiation of P19 embryonal carcinoma cells and can be prevented by bFGF (Miho et al, 1999). We have found significant increased in caspase 6, as well as caspase 3 during ES neural differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…We have noted that apoptosis during retinoic acid-induced ES differ- entiation was accompanied by increased expression of effector caspases 3 and 6. It has been reported previously that retinoic acid can induce activation of caspase-3 and cause apoptosis during neural differentiation of P19 embryonal carcinoma cells and can be prevented by bFGF (Miho et al, 1999). We have found significant increased in caspase 6, as well as caspase 3 during ES neural differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…Akt is one of the down stream targets of phosphatidylinositol 3-kinase (PI3-K) that is a signaling molecule associated with receptors of growth factors (Datta et al, 1996). PI3-K/Akt pathway has been shown to be involved in the intracellular signaling of FGF2 in cells of neural origin (Miho et al, 1999;van Weering et al, 1998) and thus should be proposed to mediate the FGF-2-induced telomerase upregulation. The role of this pathway in telomerase regulation is also sustained by studies involving PTEN, an antioncogene that exerts its role as a tumor suppressor by negatively regulating the Akt signaling pathway (Stambolic et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…When added to a variety of cell types, FGF-2 stimulates phosphoinositol-3-kinase (PI3K), which in turn activates Akt (protein kinase B). 29 Akt inhibits apoptosis by deactivating downstream targets such as BAD and forkhead transcription factor. 29,30 We previously showed that Cu 2ϩ -oxLDL downregulates endothelial FGF-2 by increasing posttranscriptional destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…29 Akt inhibits apoptosis by deactivating downstream targets such as BAD and forkhead transcription factor. 29,30 We previously showed that Cu 2ϩ -oxLDL downregulates endothelial FGF-2 by increasing posttranscriptional destabilization. 22 After pretreatment with rPAF-AH, L 5 lost the ability to inhibit FGF-2 transcription and was no longer proapoptotic.…”
Section: Discussionmentioning
confidence: 99%